Evaluasi Usability pada Website Mejakita menggunakan Metode Usability Testing - Dhiemas Gilang Pandian; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Mejakita is one of the website-based learning media that can improve student learning experiences independently and help students complete school assignments. The reason for using the MejaKita website as a usability evaluation topic is because based on the results of interviews with 11th-grade teachers majoring in Multimedia at SMK Negeri 5 Malang, recommendations for learning media are needed that can solve problems for students who have difficulty doing homework and school assignments. Initial user research conducted on 11th-grade students majoring in Multimedia at SMK Negeri 5 Malang found problems. The question content icon on the PR Discussion menu still seemed messy, it was difficult to find notes according to the school level and the desired subject, users found it difficult to write a description of the question, the comment column did not provide interaction, the arrangement of Mejakita website features is too complicated, there are problems when searching for formulas. The evaluation was carried out using the usability testing method and administering the System Usability Scale (SUS) questionnaire. The results of usability testing recommendations after calculations have obtained a value on the learnability component using the success rate equation of 24%, the efficiency component using the time-based efficiency equation gets a value of 0.07 goal/sec, the errors component using the defective rate equation gets a value of 2%, and the components satisfaction using the SUS questionnaire got a score of 71%.